Exploring identities and social networks across online and offline worlds : the couchsurfing community - Murphy, Hannah Rose (2014)
This paper examines how membership in the Couchsurfing network allows for the movement of personal relationships offline thereby redefining social interaction during tourist experiences. It also reflects the active construction of self-identity in nonymous online environments, and the reflexivity in self-identity as it is renegotiated offline during actual interaction. The study employs nineteen in-depth interviews conducted with active Couchsurfers and two instances of participant observation that took place online (on the website) and offline (during a Couchsurfing event). Findings suggest that Couchsurfers construct their online identities based on the normative expectations of the online community and their conceptions of self. During offline interaction, communal understanding and the liminality in experience aided Couchsurfers in overcoming perceived differences. They were then able to adapt their identities based on context and utilize the social capital present in the network thereby authenticating their tourist experiences.